Quality of life and social support in congestive heart failure patients‏ ‏and healthy ‎people - mEHDI Heidarzadeh; pARKHIDEH Hasani; aZIZEH Rahimzadeh; aKRAM Ghahramanian; Jafar Kolahdouzi Pour; Ilnaz Yousefi (Journal of Holistic Nursing and Midwifery)
Introduction: Congestive heart failure (CHF) is one of the most important chronic diseases in the ‎world that these patients are faced with various physical and psychological stressful factors which ‎leads to decreasing quality of life. Social support by all sources can lead to decreasing problems in ‎CHF patients and increasing quality of life in them